2012
DOI: 10.19173/irrodl.v13i4.1316
|View full text |Cite
|
Sign up to set email alerts
|

A needs assessment of ODL educators to determine their effective use of open educational resources

Abstract: <p>Nigeria has joined the global race of teaching and learning in a changing educational environment by adopting open and distance learning (ODL). Although it is a global trend, ODL poses some challenges at local levels, one of which is the untimely production of teaching materials currently affecting instructional delivery in Nigeria. The modern approach to ameliorating this challenge is the deployment of open educational resources (OER), and this practice is enabled by information and communication tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 6 publications
(2 reference statements)
1
12
0
Order By: Relevance
“…in the creation and use of OER. This is also consistent with previous research findings (Kursun et al, 2014;Okonkwo, 2012;Clements & Pawlowski, 2012). In the case of the present study, the findings indicated that the majority of the respondents (98.5%) were concerned about the IPR and copyright permissions to reuse the content.…”
Section: Discussionsupporting
confidence: 93%
“…in the creation and use of OER. This is also consistent with previous research findings (Kursun et al, 2014;Okonkwo, 2012;Clements & Pawlowski, 2012). In the case of the present study, the findings indicated that the majority of the respondents (98.5%) were concerned about the IPR and copyright permissions to reuse the content.…”
Section: Discussionsupporting
confidence: 93%
“…Nearly half of the informed students did not use the system, much like in a study by Okonkwo (2012). In the present study, the most common reasons given by students for not using the system were relevant to having adequate information on lab flyers, not needing it, and not having enough time.…”
Section: Discussionmentioning
confidence: 55%
“…Even though Carson et al (2012), Lovett, Meyer and Thille (2008), Rhoads et al (2013), and Okonkwo (2012) have indicated that the OpenCourseWare movement is a tremendous opportunity for both students and instructors, sufficient attention has not been paid to its instructional effectiveness. Most people are not aware of such systems or their benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Africa, have significantly increased the number of children attending primary and secondary schools. This is being achieved through governmental and non-governmental initiatives around e-learning, including collaborative initiatives focusing on advocacy and teacher training (Okonkwo, 2012). Davis and Fletcher's (2010) work suggest that e-learning is also being deployed in the developed countries, in an attempt to improve, simplify or supplement the existing education system.…”
Section: E-learning and Oersmentioning
confidence: 99%
“…Teacher education is indispensable if OERs are to be successful (Wright & Reju, 2012;Okonkwo, 2012). Without the knowledge of OERs' potential and how they can be accessed and used in the classroom, the availability of OERs in the primary sector becomes futile.…”
Section: Oers and Primary Educationmentioning
confidence: 99%